(untitled) (INFERENCE: Journal of English Language Teaching, 2026)
This study explores junior high school students’ trust and dependency toward ChatGPT in learning English within an Indonesian EFL context. Using a qualitative design, three students who frequently used ChatGPT were selected through purposive sampling. Data were collected through semi-structured interviews and analyzed using thematic analysis. The findings reveal that students develop conditional trust, recognizing both the usefulness and limitations of ChatGPT. Dependency varies from supportive use to strong reliance, with some students showing reduced confidence without AI assistance. While ChatGPT improves learning efficiency and accessibility, excessive reliance may reduce students’ cognitive engagement and independent problem-solving. The study highlights the importance of guided and critical use of AI tools to support learner autonomy while preventing overdependence.